2014
DOI: 10.12965/jer.140101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 16-week functional movement screen training program on strength and flexibility of elite high school baseball players

Abstract: Functional Movement Screen (FMS) is a way to pretest functional movement. This study examined the effects of the FMS training program on the strength and flexibility of 62 elite male high school baseball players (31 in the training group, 31 in the control group). All players who received less than two points on each FMS test item had to join the 16-week, three times weekly FMS training program. To analyze results among the FMS participants, measures including intraclass correlation coefficient (ICC) and repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 15 publications
3
59
0
2
Order By: Relevance
“…There are scientific studies that shows the correlation and importance of introducing functional assessment and functional training program. Hong-Sun Song et al [40] tested baseball players for functional assessment by FMS test, in which they measured functional status, strength and flexibility also. A significant impact of the training program on the improvement of functional assessment has been demonstrated, which is associated with a lower risk of injury and the probability of increased strength in the subjects has been demonstrated, and it is possible to increase flexibility, although no significant correlations were found.…”
Section: Discussionmentioning
confidence: 99%
“…There are scientific studies that shows the correlation and importance of introducing functional assessment and functional training program. Hong-Sun Song et al [40] tested baseball players for functional assessment by FMS test, in which they measured functional status, strength and flexibility also. A significant impact of the training program on the improvement of functional assessment has been demonstrated, which is associated with a lower risk of injury and the probability of increased strength in the subjects has been demonstrated, and it is possible to increase flexibility, although no significant correlations were found.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the existence of equilibrium movements such as the single-legged stand on the Bosu Ball, which are the main obstacle-stepping moves, can be a clear indication of the effectiveness of the Wrestling + warm-up program. Many studies have shown the positive impact of intervention exercises on Functional Movement Screen scores (17)(18)(19). The findings of Nemati et al (2017) also showed that after completing the four weeks of FIFA +11 warm-up, the total Functional Movement Screen score in the experimental group significantly improved (20).…”
Section: Discussionmentioning
confidence: 96%
“…Yıldız and Pınar (2013), according to the findings of the study performed on children tennis players, found that functional training method increased the vertical jump, speed, flexibility, agility, balance and functional capacity of the athletes better than the traditional training method. Song et al (2014) applied a 16-week functional training program on baseball players. According to the findings of the study, functional training increased the strength and flexibility of baseball players.…”
Section: Discussionmentioning
confidence: 99%